2018
DOI: 10.5751/ace-01193-130122
|View full text |Cite
|
Sign up to set email alerts
|

Using a natural reference system to evaluate songbird habitat restoration

Abstract: ABSTRACT. The Golden-winged Warbler (Vermivora chrysoptera) is an imperiled songbird that breeds in early-successional plant communities of eastern North America. Conservation efforts on the breeding grounds have become a priority because population declines are thought to be driven, in part, by the loss of breeding habitat. Although the species is known to use a variety of upland and wetland cover types, the majority of previous research on the species has been conducted in uplands. Although patterns of Golde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 39 publications
2
25
0
Order By: Relevance
“…Among the most efficient habitat restoration tools recommended by the Conservation Plan are overstory removal timber harvests (Bakermans et al 2015;McNeil et al 2018). Overstory removal harvests (2.2-8.9 m 2 /ha residual basal area; Bakermans et al 2011) are rigorously demonstrated to provide quality habitat for GWWA territorial establishment (Bakermans et al 2015), pairing (Roth et al 2014), andnesting (McNeil et al 2017), created from mature forest otherwise unsuitable for nesting.…”
Section: Habitat Guidelines and Restoration Implementationmentioning
confidence: 99%
“…Among the most efficient habitat restoration tools recommended by the Conservation Plan are overstory removal timber harvests (Bakermans et al 2015;McNeil et al 2018). Overstory removal harvests (2.2-8.9 m 2 /ha residual basal area; Bakermans et al 2011) are rigorously demonstrated to provide quality habitat for GWWA territorial establishment (Bakermans et al 2015), pairing (Roth et al 2014), andnesting (McNeil et al 2017), created from mature forest otherwise unsuitable for nesting.…”
Section: Habitat Guidelines and Restoration Implementationmentioning
confidence: 99%
“…At the time of biological monitoring, the managed properties were either under a current NRCS contract or had recently finished an NRCS contract to create early successional forest. Within each early-successional forest, we randomly placed 1-2 point sampling locations at which birds were surveyed (see McNeil et al [36] for point placement protocols). At each location, we conducted both American Woodcock and Golden-winged Warbler point count surveys in 2015 and 2016.…”
Section: Avian Monitoring Methodsmentioning
confidence: 99%
“…We also used point count surveys to quantify Golden-winged Warbler (and other songbird) presence but sampled during the times (early mornings) and dates (mid-May-June) when Golden-winged Warblers are best detected. See McNeil et al [36] for a full description of warbler survey methods. Our final dataset for each property included American Within each early-successional forest, we randomly placed 1-2 point sampling locations at which birds were surveyed (see McNeil et al [36] for point placement protocols).…”
Section: Avian Monitoring Methodsmentioning
confidence: 99%
See 2 more Smart Citations